If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2x + 4 + -5 = 3x + -1 Reorder the terms: 4 + -5 + 7x + -2x = 3x + -1 Combine like terms: 4 + -5 = -1 -1 + 7x + -2x = 3x + -1 Combine like terms: 7x + -2x = 5x -1 + 5x = 3x + -1 Reorder the terms: -1 + 5x = -1 + 3x Add '1' to each side of the equation. -1 + 1 + 5x = -1 + 1 + 3x Combine like terms: -1 + 1 = 0 0 + 5x = -1 + 1 + 3x 5x = -1 + 1 + 3x Combine like terms: -1 + 1 = 0 5x = 0 + 3x 5x = 3x Solving 5x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5x + -3x = 3x + -3x Combine like terms: 5x + -3x = 2x 2x = 3x + -3x Combine like terms: 3x + -3x = 0 2x = 0 Divide each side by '2'. x = 0 Simplifying x = 0
| x-60=-17/2(y-20) | | 8p-p+14=1-6p | | 7x+3*(2x-4)=0 | | 2x+3x+7=-43 | | 2(v+8)=9v-47 | | -10=-8v+2(v-8) | | 18+16-5+4= | | -1=-8+x/-2 | | -16y(y-18)= | | 6(x-11)=x+9 | | 2.5k+5-1.5k=14 | | a/-3+3=8 | | z=5-28z | | 7(3m-5)-5(1+m)=0 | | 0=-16t^2+20t+24 | | x^3+x^2-12x-10=0 | | x/23=0.5 | | 55-6(3b-1)=-11 | | x/23=50 | | 9X1/2=38 | | 16y-8xy+yx^2=0 | | 4y-8y=5 | | 13=4x-9 | | 4+x=5x | | -131=-8(m+7)-7m | | 3(d-8)-5=9(9d+2)+1 | | -105=6(3r-4)-9r | | -49-9v=2-7(v+5) | | 4+3a-8-2a= | | y/4=-5-6 | | 7y+6+4y-13=26 | | 17=4x-4-(-3x) |